2004
DOI: 10.1177/076737010401900407
|View full text |Cite
|
Sign up to set email alerts
|

Proposition d'échelle de mesure de l'authenticité perçue d'un produit alimentaire

Abstract: L'authenticité représente un axe stratégique pour positionner son offre. Cependant le milieu professionnel et académique manque d'outils pour répondre au mieux à la quête d'authenticité. Notre article apporte une définition du concept et étudie ses facettes en partant d'une revue de la littérature et des représentations des consommateurs. Deux terrains qualitatifs ainsi que trois terrains quantitatifs permettent de construire un instrument de mesure appliqué au domaine alimentaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 34 publications
1
28
0
8
Order By: Relevance
“…Hypothesis H10a is affirmed by our data. These results complete the literature on terroir store brands by highlighting that terroir store brands may create attachment to them through perceived authenticity (Camus, 2004a) and perceived value (Khan, 2010;Luarn and Lin, 2003;Lai, 2015), and that distinguishes these specific SBs from economic and standard SBs. Indeed, to our knowledge, previous works on store brands (Binniger, 2007;Belaid et al, 2016) have not demonstrated consumers' attachement to these brands.…”
Section: Impacts Of the Perceptions Of The Product: Role Of Perceivedmentioning
confidence: 60%
See 3 more Smart Citations
“…Hypothesis H10a is affirmed by our data. These results complete the literature on terroir store brands by highlighting that terroir store brands may create attachment to them through perceived authenticity (Camus, 2004a) and perceived value (Khan, 2010;Luarn and Lin, 2003;Lai, 2015), and that distinguishes these specific SBs from economic and standard SBs. Indeed, to our knowledge, previous works on store brands (Binniger, 2007;Belaid et al, 2016) have not demonstrated consumers' attachement to these brands.…”
Section: Impacts Of the Perceptions Of The Product: Role Of Perceivedmentioning
confidence: 60%
“…These perceptual elements have encouraged both manufacturers and retailers to affix the term terroir to their respective offers. However, this poses a risk of instrumentalization (Camus, 2004a). Therefore, one of the elements that could capture the credibility of the terroir positioning, and in turn its positive perceptions by consumers, is the concept of perceived authenticity (Camus, 2004a).…”
Section: Authenticity and Perceived Value Of Terroir Sbmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, authenticity can be approached in several ways: objective authenticity is based on originality and the genuineness of objects and sites, as verified by experts (Kolar & Zabkar, 2010;Ram et al, 2016); constructive authenticity is determined by the tourist and is subjective, negotiable, and contextual (Ram et al, 2016); and experiential authenticity refers to the subjective tourism experience (Wang, 1999). Referring to food products, Camus (2004) proposes three main components: origin, uniqueness, and projection. An authentic product first is determined by its origin, but it also is exclusive in nature, with no possibility of imitation.…”
Section: Local Distinctivenessmentioning
confidence: 99%